2017
DOI: 10.13102/sociobiology.v64i1.1179
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric diversity and phylogenetic relationships among Iranian honey bee (Apis mellifera meda Skorikow, 1829) populations using morphological characters

Abstract: In this study, the morphometric diversity and phylogenetic relationships of Iranian honey bee populations, were investigated using 14 morphometric characteristics. A total of 2250 young adult worker bees from 20 different populations in 20 different provinces of Iran were collected during June to October 2014. The results of nested analysis of variance showed that there were significant differences (P<0.01) between the provinces for all analyzed morphometric traits indicating the existence of a diversity am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In a recent study of Iranian honey bee samples, we earlier showed that all honey bee samples then tested belonged to the East Mediterranean (C) lineage as found using several restriction enzymes and morphological characters (Rahimi, 2015b;Rahimi et al, 2017). In the present study, we have used different two mtDNA regions with different samples of the mitochondrial genome to verify the nature and distribution of genetic variation within and between Iranian honey bee populations.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In a recent study of Iranian honey bee samples, we earlier showed that all honey bee samples then tested belonged to the East Mediterranean (C) lineage as found using several restriction enzymes and morphological characters (Rahimi, 2015b;Rahimi et al, 2017). In the present study, we have used different two mtDNA regions with different samples of the mitochondrial genome to verify the nature and distribution of genetic variation within and between Iranian honey bee populations.…”
Section: Discussionmentioning
confidence: 82%
“…Honey bee race in this region include the subspecies A. m. meda (Ruttner, 1988). Honey bee subspecies from Iran was studied extensively using morphometric and izoenzymic analysis (Moradi & Kandemir, 2004;Rahimi & Asadi, 2010;Rahimi & Mirmoaydi, 2013;Rahimi et al, 2014a,b;Rahimi et al, 2015a;Rahimi et al, 2017); molecular markers, mitochondrial DNA (mtDNA) analysis (Rahimi et al, 2014a,b;Rahimi et al, 2015b;Rahimi et al, 2016); microsatellite and RAPD analysis (Royan et al, 2007;Kamrani et al, 2012;Rahimi et al, 2014a,b). More recently, genetic systems such as allozymes (Nunamaker & Wilson, 1982;Badino et al, 1988), nuclear DNA (Hall, 1990;Tarès et al, 1993), mitochondrial DNA (mtDNA) (Moritz et al, 1986;Smith et al, 1989Smith et al, , 1991Hunt & Page, 1992;Garnery et al, 1993;Oldroyd et al, 1995;Arias and Sheppard, 1996;Pedersen, 1996;De la Rùa et al, 2000) and microsatellites (Estoup et al, 1993;Garnery et al, 1998) have been used to study honey bee diversification.…”
mentioning
confidence: 99%
“…To date, no In-silico studies exploring IgEmediated honey bee allergies have been reported so far in the world and the Ha'il region of Saudi Arabia (32). There have already been some studies related to the molecular genetics of honey bees (33)(34)(35). The potential allergens predicted using our immunoinformatic approach can be used to design potential prophylactic peptide vaccine candidates for reducing the allergic response associated with honey bee venom in the Ha'il region of Saudi Arabia and regions/countries (China, Turkey, Canada, United States and India) prone to honey bee attack and farming.…”
Section: Discussionmentioning
confidence: 99%
“…Many molecular markers such as restriction fragment length polymorphism (RFLP), random amplified polymorphic DNA (RAPD) and mitochondrial DNA (mtDNA) analyses have been used in honey bee population genetics studies, but for the last 20 years, microsatellite loci have been quite widely used due to their features such as high polymorphism, multiallelicity, abundance in the genome and easy scorable (Kandemir & Kence, 1995;Smith et al, 1997;Bodur et al, 2007;Kekeçoğlu et al, 2009;Özdil et al, 2009;Liu et al, 2016;Rahimi et al, 2016;Haddad et al, 2018;Hassett et al, 2018;Yu et al, 2019;Özdil et al, 2022). Latterly, single nucleotide polymorphisms (SNPs) have been used in population genetics studies, however, thanks to the advantages provided by microsatellites, they could not get ahead of microsatellites even in the genomic era (Zimmerman et al, 2020;Mukherjee et al, 2022;Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%